Suscetibilidade e reversão da resistência a inseticidas em população de Aedes (Stegomya) Aegyti(Linnaeus, 1762) (Diptera: Culicidae) - Vieira, Thalita Bastida (2015)
Orientador : Prof. Dr. Mário Antônio Navarro da Silva